2019
DOI: 10.1216/rmj-2019-49-3-773
|View full text |Cite
|
Sign up to set email alerts
|

Lagrange's theorem for Hom-Groups

Abstract: Hom-groups are nonassociative generalizations of groups where the unitality and associativity are twisted by a map. We show that a Hom-group (G, α) is a pointed idempotent quasigroup (pique). We use Cayley table of quasigroups to introduce some examples of Hom-groups. Introducing the notions of Hom-subgroups and cosets we prove Lagrange's theorem for finite Hom-groups. This states that the order of any Hom-subgroup H of a finite Hom-group G divides the order of G. We linearize Homgroups to obtain a class of no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Throughout this paper, we consider regular Hom-groups that is the case when the structure map is invertible, and this notion can be traced back to Caenepeel and Goyvaerts's pioneering work [3]. The axioms in the following definition of Hom-group is different from the one in [7,8,13]. However, we show that if the structure map is invertible, then some axioms in the original definition are redundant and can be obtained from the Hom-associativity condition.…”
Section: Hom-groupsmentioning
confidence: 99%
See 2 more Smart Citations
“…Throughout this paper, we consider regular Hom-groups that is the case when the structure map is invertible, and this notion can be traced back to Caenepeel and Goyvaerts's pioneering work [3]. The axioms in the following definition of Hom-group is different from the one in [7,8,13]. However, we show that if the structure map is invertible, then some axioms in the original definition are redundant and can be obtained from the Hom-associativity condition.…”
Section: Hom-groupsmentioning
confidence: 99%
“…Remark 2.11. Note that the definition of a Hom-group in [8] consists of the axiom Φ(e Φ ) = e Φ . In Proposition 2.13, we show that this axiom is redundant in the regular case.…”
Section: Hom-groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, M. Hassanzadeh developed representations and a (co)homology theory for Hom-groups in [7]. He also proved Lagrange's theorem for finite Hom-groups in [8]. In [9], Hom-Lie groups and relationship between Hom-Lie groups and Hom-Lie algebras were explored.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that a Homassociative algebra gives rise to a Hom-Lie algebra using the commutator. Since then, various Hom-analogues of some classical algebraic structures have been introduced and studied intensively, such as Hom-coalgebras, Hom-bialgebras and Hom-Hopf algebras [24,25], Hom-groups [26,27], Hom-Hopf modules [28], Hom-Lie superalgebras [29,30], generalize Hom-Lie algebras [31], and Hom-Poisson algebras [32].…”
Section: Introductionmentioning
confidence: 99%